2012
DOI: 10.1177/1043454212439472
|View full text |Cite|
|
Sign up to set email alerts
|

Posttraumatic Growth, Coping Strategies, and Psychological Distress in Adolescent Survivors of Cancer

Abstract: Only recently have researchers begun to empirically examine positive outcomes such as posttraumatic growth in adolescent cancer. This article examines associations between posttraumatic growth, coping strategies, and psychological distress in adolescent cancer survivors. Adolescents who finished cancer treatment 2 to 10 years prior (N = 31) completed self-report measures of posttraumatic growth, coping, symptomatology, and disease-related characteristics. Younger age at diagnosis and less use of avoidant copin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
3
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 51 publications
4
64
3
11
Order By: Relevance
“…We identified 17 studies examining PTG in parents of children with pediatric disease 5,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] (see Table 1), 7 studies that demonstrated PTG or benefit finding in children with pediatric disease [42][43][44][45][46][47][48] (see Table 2), and 2 that included both parents and pediatric patients. 49,50 We summarize the findings from these studies in the nine components of our conceptual model of SPI-PTG: (1) the nature and subjective experience of the traumatic event, (2) trauma and the disruption of a personal worldview, (3) PTG as rebuilding or reshaping this worldview, (4) elements of SPI-PTG, (5) cognitive processing underlying SPI-PTG, (6) affective processing underlying SPI-PTG, (7) posttraumatic afterevents, (8) individual characteristics affecting SPI-PTG, and (9) social support affecting SPI-PTG (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 17 studies examining PTG in parents of children with pediatric disease 5,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] (see Table 1), 7 studies that demonstrated PTG or benefit finding in children with pediatric disease [42][43][44][45][46][47][48] (see Table 2), and 2 that included both parents and pediatric patients. 49,50 We summarize the findings from these studies in the nine components of our conceptual model of SPI-PTG: (1) the nature and subjective experience of the traumatic event, (2) trauma and the disruption of a personal worldview, (3) PTG as rebuilding or reshaping this worldview, (4) elements of SPI-PTG, (5) cognitive processing underlying SPI-PTG, (6) affective processing underlying SPI-PTG, (7) posttraumatic afterevents, (8) individual characteristics affecting SPI-PTG, and (9) social support affecting SPI-PTG (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…38,[52][53][54] Correspondingly, in pediatric studies the objective severity level of medical illness or risks of treatment are generally not associated with the degree of posttraumatic stress or PTG in parents or patients (although two studies have shown that PTG varies with type of diagnosis). 1,10,40,[47][48][49][50] Trauma and the disruption of a personal worldview Every individual has his or her own personal understanding of and perspective on the world and interprets life events within the context of this perspective, termed the ''assumptive world.'' This assumptive world consists of a set of cognitive constructs known as ''schemas,'' the basic units of one's understanding of oneself and the world.…”
Section: Nature Of Traumatic Events and Subjective Experience Of Traumamentioning
confidence: 99%
See 1 more Smart Citation
“…From the article published by Turner-Sack et al [88], it is apparent that it is imperative to conduct such research on adolescent cancer patients. The need for this stems from other research work conducted on these populations which shows maturity and emotional growth as a result of the disease.…”
Section: Aspects Of Disease and Treatments In Ayas Based On The Qualimentioning
confidence: 99%
“…The chances for a relapse are higher among patients reporting a lower posttraumatic growth. Focusing on positive aspects also leads to positive posttraumatic growth [88]. …”
Section: Aspects Of Disease and Treatments In Ayas Based On The Qualimentioning
confidence: 99%